2021
DOI: 10.1159/000517965
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Chitosan on Facial Skin Sebum

Abstract: Introduction: Seborrhea or oily skin has been one of the most common complaints affecting both men and women physically and psychologically. Chitosan is a biopolymer obtained from the alkaline deacetylation of chitin. Due to its positively charged nature, chitosan can effectively bind to lipids. Therefore, chitosan nanoparticle (CN) formulation may benefit in the reduction of skin sebum. Objective: The aim of this study was to evaluate the efficacy and safety of CN formulation in the reduction of skin sebum. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…Due to the positive charge on chitosan, it can act as a humectant to maintain skin moisture or strengthen hair and act as a conditioner through interactions with hair keratin [ 126 ]. Suspensions of chitosan nanoparticles in guar gum have been indicated to reduce skin sebum levels in seborrhea patients [ 127 ]. Azimi et al found that chitin nanofibrils electrosprayed onto cellulose films improved compatibility with skin cells and downregulated inflammatory cytokines, indicating potential applications for nanochitin in cosmetics [ 128 ].…”
Section: Applicationsmentioning
confidence: 99%
“…Due to the positive charge on chitosan, it can act as a humectant to maintain skin moisture or strengthen hair and act as a conditioner through interactions with hair keratin [ 126 ]. Suspensions of chitosan nanoparticles in guar gum have been indicated to reduce skin sebum levels in seborrhea patients [ 127 ]. Azimi et al found that chitin nanofibrils electrosprayed onto cellulose films improved compatibility with skin cells and downregulated inflammatory cytokines, indicating potential applications for nanochitin in cosmetics [ 128 ].…”
Section: Applicationsmentioning
confidence: 99%
“…Gangguan kesehatan kulit yang sering dialami oleh pasien di Klinik Nanisa adalah pembesaran pori-pori wajah, komedo, dan telangiactasis. Gangguan kesehatan yang pertama adalah pori-pori wajah yang membesar dapat disebabkan oleh perbedaan jenis kelamin, kecenderungan genetik, penuaan, paparan sinar ultraviolet kronis, xenobiotik komedogenik, jerawat, dan seborrhoea [10]. Selain pori-pori membesar, komedo juga menjadi permasalahan yang sering ditemui pada pasien.…”
Section: Pendahuluanunclassified
“…Thus, the interaction between the positive charges of the chitosan backbone and the anionic charges of the skin surface can be exploited as a very promising tool for ensuring the targeted release of cleaners [70]. Moreover, Theerawattanawit et al [71] demonstrated that chitosan gels may be exploited for reducing sebum levels without any side effects.…”
Section: Skin Cleansingmentioning
confidence: 99%